Pengaruh Keberadaan Jentik dan Perilaku 3M Plus terhadap Kejadian Demam Berdarah Dengue - Siregar, Saadah; Mulyani, Sri; Rizky, Vincentia Ade; Akmal, Dzul; Sutriyawan, Agung (LPPM Hang Tuah Pekanbaru, 2023)
An infectious disease that is still a public health problem today is dengue hemorrhagic fever. Prevention efforts that can be done are by breaking the chain of transmission by eradicating mosquito nests. The purpose of this study is to analyze the influence of the presence of larvae and the behavior of 3M plus on the incidence of dengue hemorrhagic fever. The study used a cross-sectional design. The research was carried out in the working area of Puskesmas Puter, in July - August 2022. The population in this study was 7,110 heads of households. The number of samples was 67 heads of families, taken using stratified random sampling techniques. The statistical test used is the chi-square test. The results showed that the variables that affect the incidence of dengue hemorrhagic fever are the presence of larvae (p = 0.006 and POR = 4.8), closing water reservoirs (p = 0.009 and POR = 4.8), draining water reservoirs (p = 0.041 and POR = 3.5), and larvicides (p = 0.027 and POR = 4.4). This research can conclude that the incidence of DHF can be influenced by several factors, namely the presence of mosquito larvae, and the behavior of closing, draining, and sprinkling larvicide powder. It is recommended that health workers further optimize the role of levels in monitoring mosquito nest eradication behavior carried out by the community.